How Can Business Share Responsibility for Disaster Resilience?. Issue 3 (17th June 2018) - Hunt, Susan; Eburn, Michael
Abstract: This paper contributes to knowledge of disaster resilience policy implementation in Australia and proposes measures to strengthen partnerships between government and the business sector to enhance national disaster resilience capacity. In Australia, business makes a significant contribution to disaster relief and recovery. Even so, there are unexplored opportunities to enhance the role of business in disaster resilience, particularly through partnerships with government. The extent that state, regional and local‐level disaster plans engage business in disaster relief and recovery is described and their relatively less prominent involvement in disaster resilience is discussed. Examples of disaster resilience policies and their capacity to influence business practices to support disaster resilience are introduced with suggestions for how they can be enhanced. Some potential benefits and pitfalls of public–private sector collaboration are explored and it is noted that, in disaster resilience settings, these risks can be ameliorated through appropriate implementation. Abstract : This paper examines the contribution that business makes to disaster resilience in Australia and suggests measures to enhance this contribution. This can primarily be achieved by building mutual trust through closer business and government engagement throughout the disaster management cycle including formal public–private partnerships and/or less formal working relationships.